Cultural capital and higher education choices of Thai youth - Wongburanavart, Chanoknart (2021)
Employing perspectives from Bourdieu's theory of practice on the three key concepts: cultural capital, habitus and field, the objective of this study is to explain the impact of cultural capital on Thai students’ choices of education and careers after graduating from secondary education. The study draws on quantitative and qualitative data of students from different socio-cultural backgrounds to explore their life stories and factors in relation to the notions of practice, habitus and field; and how these interrelations generate forms of cultural capital which also tend to be passively inherited within particular social groups through the context of social value, socio-cultural roles, and norms. In Thailand, higher education could play an important role in enabling upward social and economic mobility, and eliminating social inequality; as higher education institutions are sources of knowledge and skills, filled with different forms of capitals which could enhance the social opportunities of the participants. However, higher education in Thailand has so far failed to adequately address the problem of social inequality; its existence remains widespread. Investigating the higher education recruitment system in Thailand and the cultural capital required within the field, in addition to other practices within and/or between each social field in Thai society, the analysis showed that cultural capital is the key hindrance to students from under-privileged social groups in securing access to higher education. Thus, in order to enhance the role of higher education in reducing inequality in the society, widening participation in higher education should be a major component of government education policy in Thailand. Nevertheless, the root causes of social reproduction should not be overlooked.